The U.S. economy in WWII as a model for coping with climate change - Hugh Rockoff (Rutgers University, Department of Economics, 2016)
During World War II the United States rapidly transformed its economy to cope with a wide range of scarcities, such as shortfalls in the amounts of ocean shipping, aluminum, rubber, and other raw materials needed for the war effort. This paper explores the mobilization to see whether it provides lessons about how the economy could be transformed to meet scarcities produced by climate change or other environmental challenges. It concludes that the success of the United States in overcoming scarcities during World War II without a major deterioration in living standards provides a basis for optimism that environmental challenges can be met, but that the unique political consensus that prevailed during the war limits the practical usefulness of the wartime model.
Keywords: N4; 330; World War II; climate change; infrastructure; Klimapolitik; Rohstoffpolitik; Energieversorgung; Vergleich; Kriegswirtschaft; Rationierung; USA